2016
DOI: 10.5539/elt.v9n4p171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Culture-Specific Items and Translation Strategies Applied in Translating Jalal Al-Ahmad’s by the Pen

Abstract: Due to differences across languages, meanings and concepts vary across different languages, too. The most obvious points of difference between languages appear in their literature and their culture-specific items (CSIs), which lead to complexities when transferring meanings and concepts from one language into another. To overcome the complexities arisen from the distinction between languages in the process of translation, translation scholars have proposed different strategies. Newmark's proposed taxonomy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…This term has no one-to-one target equivalent in English. Senior students of a translation program should have by that level gained the appropriate instruction as to which strategies to employ in such culture-bound terminology (Newmark, 1988;Dickens et al, 2002;Elewa, 2015;Daghoughi & Hashemian, 2016) . About (35 %) of the participants opted for the couplet strategy.…”
Section: Translation Analysismentioning
confidence: 99%
“…This term has no one-to-one target equivalent in English. Senior students of a translation program should have by that level gained the appropriate instruction as to which strategies to employ in such culture-bound terminology (Newmark, 1988;Dickens et al, 2002;Elewa, 2015;Daghoughi & Hashemian, 2016) . About (35 %) of the participants opted for the couplet strategy.…”
Section: Translation Analysismentioning
confidence: 99%
“…results of the analysis revealed that through (loan) translation was the most frequently used procedure. Daghoughi and Hashemian (2016) investigated Newmark's procedures to determine the most useful procedure in translating culture-specific items applied in the English translation of Jalal Al-Ahmad's By the Pen. The results of the study revealed that the functional equivalent was the most frequent translation procedure applied while translating a literary text from Persian into English and that modulation and paraphrase were the least frequent translation procedures applied.…”
Section: Textsmentioning
confidence: 99%
“…In the process of studying literary translation, a culturallinguistic personality of the translator-to-be should transform into a self-growing, emotionally mature intellectually cognitive organism capable to cope with unforeseen culture-conditioned translation situations [7,8]. The translator should possess dynamism, which allows one to constantly both strengthen and modify one's own ideas about one's own culture and the culture the source text belongs to in order to create a full-fledged translation [9].…”
Section: Translator Competences and Qualitiesmentioning
confidence: 99%